2010
DOI: 10.1007/s00167-010-1351-6
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-six years of meniscal allograft transplantation: is it still experimental? A meta-analysis of 44 trials

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
236
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 223 publications
(246 citation statements)
references
References 68 publications
6
236
0
4
Order By: Relevance
“…7 A meta-analysis and clinical studies have shown comparable outcomes between the 2 different fixation techniques. 2,4,8 Although both techniques are viable options for meniscal allograft fixation, the technique described in this report provides a reliable method for surgeons to undertake meniscal transplantation.…”
Section: Discussionmentioning
confidence: 97%
“…7 A meta-analysis and clinical studies have shown comparable outcomes between the 2 different fixation techniques. 2,4,8 Although both techniques are viable options for meniscal allograft fixation, the technique described in this report provides a reliable method for surgeons to undertake meniscal transplantation.…”
Section: Discussionmentioning
confidence: 97%
“…Overall, clinical and functional outcomes are satisfactory, and MAT is currently considered a safe, reliable and justified procedure in selected patients [6,7,9,12,13]. During the first 5 years after MAT, physicians can expect a mean Lysholm score of 80 points (range 60-100), with still values between 60 and 80 points at a follow-up between 10 and 20 years [7]. Also, several studies have reported a significant improvement in postoperative values of the Lysholm score compared to preoperative values [14][15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, concomitant focal high-grade chodral osteochondral defects in the affected compartment, unacceptable axial malalignment or knee instability have to be corrected before or during MAT. Therefore, concomitant procedures such as cartilage repair, anterior cruciate ligament reconstruction, or tibial/femoral osteotomy can be also performed in the same operation [7][8][9]. Although some studies have reported acceptable results with MAT in patients with advanced cartilage defects (grades III and IV of the Outerbridge grading system) in terms of graft survival, pain relief, and function improvement [10,11], it is advisable to perform the MAT before these changes occur [9].…”
Section: Indications and Contraindicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recently published meta-analysis, analysing 44 published clinical trials with at least 6 months follow-up in the last 26 years, concluded that this procedure should not be considered experimental surgery anymore, but, instead, it is a safe and effective technique allowing patients to resume high levels of activity and work, at least, as a longterm ''bridging'' procedure before arthroplasty (Elattar et al, 2011). Actually, a number of orthopaedic surgeons have reported clinical and radiological mid-term results (Kim et al, 2012;Lee and Caborn, 2012).…”
Section: Meniscal Transplantationmentioning
confidence: 99%